Percutaneous Thrombin Injection with Balloon Protection for a Large Iatrogenic Femoral Artery Pseudoaneurysm: A Case Report with Review of Literature - Patel, Ranjan; Tripathy, Tara Prasad; Debbarma, Ripan; Mohakud, Sudipta; Mohanty, Satyapriya; Deep Bag, Nerbadyswari (Acta medica Lituanica, 2023)
Iatrogenic femoral artery pseudoaneurysms (IFAPs) are not uncommon due to the increase in various minimally-invasive endovascular procedures. Percutaneous thrombin injection is an established technique for large pseudoaneurysms. When ultrasound-guided compression of an aneurysmal neck is not feasible, percutaneous thrombin injection can be combined with endovascular balloon occlusion to prevent leakage of thrombin into the parent artery. We describe a large IFAP following the removal of the femoral dialysis catheter after an inadvertent arterial puncture, which was managed with percutaneous ultrasound-guided (USG) thrombin injection with simultaneous balloon occlusion at the level of the aneurysmal neck without any complications. Follow-up imaging showed thrombosed IFAP without any recurrence.